2022
DOI: 10.3390/ijerph19105810
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Radon Activity Concentration—A MetroRADON International Intercomparison

Abstract: An international comparison of continuous monitors measuring radon activity concentration was performed to validate the traceability of the European radon calibration facilities. It was carried out by comparing the secondary standards used by these previous facilities, ranging from 100 Bq·m−3 to 300 Bq·m−3. Secondary standards were individually compared to a secondary reference device previously calibrated in a reference radon atmosphere traceable to a primary standard. The intercomparison was organized by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It is also known, that at very low radon concentrations such equipment tends to misread the real values as it cannot respond quickly enough to record small, but fast changes. Also, it was demonstrated that even detectors of the same model can significantly deviate from the reference value at low radon concentrations ( 9 ) .…”
Section: Resultsmentioning
confidence: 99%
“…It is also known, that at very low radon concentrations such equipment tends to misread the real values as it cannot respond quickly enough to record small, but fast changes. Also, it was demonstrated that even detectors of the same model can significantly deviate from the reference value at low radon concentrations ( 9 ) .…”
Section: Resultsmentioning
confidence: 99%
“…At this moment, in Asian countries, international intercomparisons are organized ad hoc without coordination between countries. To date, none of the existing radon chambers in Asia has been accredited to the ISO 17025 standard, in contrast to Europe, where many scientific institutes and companies are accredited, e.g., BfS in Germany [171] and SÚJCHBO in the Czech Republic [172]. In Europe, the BSS, which must be transposed into national legislation by EU member states, and which requires establishing a national radon action plan, has proven to be a powerful incentive for developing a radon abatement policy, and has motivated many national and international research projects.…”
Section: Information Exchange and Logistical Harmonizationmentioning
confidence: 99%
“…Within the MetroRADON project framework, the SUJCHBO laboratory in the Czech Republic performed and coordinated the intercomparison of secondary standards in the range of 200–300 Bq·m [ 5 ]. Eight laboratories from eight European countries participated in this exercise.…”
mentioning
confidence: 99%